2016
DOI: 10.1126/science.aad2450
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of a native, fully glycosylated, cleaved HIV-1 envelope trimer

Abstract: The envelope glycoprotein trimer (Env) on the surface of HIV-1 recognizes CD4+ T cells and mediates viral entry. During this process, Env undergoes large conformational rearrangements making it difficult to study in its native state. Soluble, stabilized trimers have provided valuable insights into Env structure, but they lack the hydrophobic membrane proximal external region (MPER), which is an important target of broadly neutralizing antibodies (bnAbs), the transmembrane domain and the cytoplasmic tail (CT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
609
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(641 citation statements)
references
References 63 publications
31
609
1
Order By: Relevance
“…1 A and B). The BG505 Env in this complex adopts a conformation that is more open than the closed conformation in crystal and EM structures of Env trimers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), but less open than the conformation in low-resolution sCD4-bound Env structures (4-7) (Figs. 2 A and B and 3A) and an ∼9-Å cryo-EM reconstruction of the KN1144 SOSIP.681 soluble trimer bound to 17b in the absence of sCD4 (7).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…1 A and B). The BG505 Env in this complex adopts a conformation that is more open than the closed conformation in crystal and EM structures of Env trimers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), but less open than the conformation in low-resolution sCD4-bound Env structures (4-7) (Figs. 2 A and B and 3A) and an ∼9-Å cryo-EM reconstruction of the KN1144 SOSIP.681 soluble trimer bound to 17b in the absence of sCD4 (7).…”
Section: Resultsmentioning
confidence: 98%
“…Single-particle electron microscopy (EM) structures of recombinant native-like soluble Env gp140 trimers (SOSIPs) confirmed that they can adopt the same closed and open architectures as virion-bound Env trimers (5-7), thus the SOSIP substitutions (introduction of a disulfide bond linking gp120 to gp41 and an Ile→Pro mutation in gp41; ref. The closed conformation of HIV-1 Env is stabilized by interactions at the trimer apex mediated by the gp120 V1V2 loop (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In the closed state, the V1V2 region shields the binding site for the coreceptor on the V3 loop (11, 16), but V1V2 interactions with V3 cannot be maintained when the gp120 protomers rotate and separate to create the CD4-bound open conformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies of bNAbs bound to HIV Env trimers revealed mechanisms by which bNAbs targeting various epitopes penetrate the glycan shield to either accommodate or include N-glycans in their epitopes (Julien et al, 2013;Pancera et al, 2014;Scharf et al, 2015;Garces et al, 2015;Lee et al, 2015Lee et al, , 2016Stewart-Jones et al, 2016). However, because heterogeneous glycosylation generally prevents the formation of well ordered crystals, all HIV Env crystal structures had been solved using glycoproteins produced in exclusively high-mannose forms (Diskin et al, 2011(Diskin et al, , 2013Kwon et al, 2015;Garces et al, 2015;Julien et al, 2013;Pancera et al, 2014;Scharf et al, 2014Scharf et al, , 2015StewartJones et al, 2016;Zhou et al, 2010Zhou et al, , 2013Zhou et al, , 2015Kwong et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Chu, Maltsev, Emwas, & Lorigan, 2010;Schnell & Chou, 2008). Very recently, cryo-EM is providing more structural information especially on huge membrane protein complexes (Byeon et al, 2009;Lee, Ozorowski, & Ward, 2016;X. Zhang, Jin, Fang, Hui, & Zhou, 2010).…”
mentioning
confidence: 99%